Socio-Behavioral Changes in Dava Village: The Influence of the Gunung Botak Gold Mine - Rusdi, M.; P, Reski; Hajar, Ibnu; Papuangan, Astriyani A. (Journal of Ecohumanism, 2024)
This study aims to describe the influence of the Gunung Botak gold mine on behavioral changes and identify the factors driving socio-economic shifts within the community of Dava Village, Buru Regency. A qualitative descriptive approach was employed, with purposive sampling used to select informants based on predetermined criteria aligned with the research objectives. Data collection was carried out through observations, interviews, and documentation. The data were analyzed through stages of reduction, presentation, verification, and conclusion drawing. The findings reveal significant social and economic impacts of the mining activities. Socially, the mine has disrupted social structures, triggering tension and conflict due to shifts in roles and inequitable distribution of mining benefits. These changes have led to polarization, distrust, altered communication patterns, and increased violence and aggression. Economically, many residents have shifted their livelihoods to mining, resulting in higher incomes that influence consumption patterns, lifestyle changes, and the emergence of new social status symbols. Several factors contribute to these socio-economic changes, including economic pressures from the mine, migration and urbanization, environmental impacts, and cultural and value shifts. Collectively, these factors reflect a complex and multidimensional socio-economic phenomenon caused by the presence of the gold mine.